An investigation of the relative efficiencies of lambda expressions and combinators - Peyton Jones, Simon (Proc ACM symposium on Lisp and functional programming, 1982)
In "A new implementation for applicative languages" Turner uses combinators to implement lambda expressions. This paper describes an experimental investigation of the efficiency of Turner's technique compared to more traditional reducers.